MAIN ASPECTS OF COMPLEX ESTIMATION OF GEOLOGICAL ENVIRONMENTAL SATATE FOR NATURE-TECHNOGEN TRANS-PIPE SYSTEMS IN WESTERN SIBERIA - IVANIK, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Analytical blocks of the geologic environment have been analyzed for the purpose of complex estimation of influence on transcontinental pipelines system. Characteristic of the geological environmental components in Western Siberia has been presented.